Clash of Class in Susanna White's Jane Eyre Miniseries Movie (2006): a Marxist Approach - NURCHOTIMAH, SATI (2011)
This research paper is primarily intended to identify how the clash of class in Susanna White's Jane Eyre miniseries (2006) viewed from Marxist's perspective, and to analyze the movie based on its structural elements. In analyzing the moviel, the writer uses descriptive qualitative study that it has data in the forms of written or oral from observing people or behavior and Marxist perspective. The type of the data is text and image. The data sources consist of primary data and secondary data sources. The primary data source is the play of Susanna White's Jane Eyre miniseries movie itself and the secondary data are the sources that relate to the primary data, such as author's biography, books and website relate to class conflict of Marxist Approach. The data are collected by using two kinds of technique: note taking and image capturing. The technique of data analysis consists of three steps: classifying the data, verifying the data and interpreting the data. The research significance is to give contribution to the body of knowledge, particularly the literary study on Susanna White's Jane Eyre miniseries movie. The outcome of the study shows in the following conclusion. First, Susanna White gives the different motion in this miniseries movie; she gives many aspects of Jane Eyre's life so that the writer might choose the appropriate theory to analyze it. Second, based on Marxist Approach, there is a clash of class in this miniseries movie, many differences between the high social class and low social class. And the last, there are many ways to face the clash of class, not only with the struggle, because from this miniseries movie, Jane faces her problem with honest, criticality, calm and sincerity.